The Involvement of Parents in the Children’s Care Process; a Comparison of Various Countries - Budiarti Santoso, Meilanny (EMPATI: Jurnal Ilmu Kesejahteraan Sosial, 2018)
Abstract. To be a parent means to put the commitment of time and unselfish self during serving as a parent as well as spouse, part of big family, friends, and colleagues. Someone is becoming a parent because adults have been prepared to respond positively to the existing of a baby as well as strong community drive as the influence to have children. This article is aiming at describing the parental involvement in child care influenced by culture and geographical location of their living. This article is formulated using literature study on child care practices around the world. Parent is defined as individuals who provide care, protection, and guidance since the baby until growing up. During conducting their role in providing care, guidance and needs fulfillment, the parent is very much influenced by culture and geographical location. Therefore the role and parental involvement in child care practice are unique in every region/country.Abstrak. Menjadi orang tua berarti menempatkan komitmen waktu dan tak mementingkan diri sendiri selama berperan sebagai orang tua dan suami/istri, bagian dari keluarga besar, teman dan kolega. Seseorang yang sedang menjadi orang tua dikarenakan masa dewasa yakni sudah disediakan untuk merespon secara positif kehadiran bayi. Juga dukungan dan pengaruh kuat dari masyarakat agar memiliki anak. Artikel ini bertujuan menggambarkan keterlibatan orang tua dalam mengasuh anak yang dipengaruhi oleh kebudayaan dan lokasi geografis tempat tinggal. Artikel ini disusun menggunakan studi pustaka tentang praktik pengasuhan anak di dunia. Orang tua diartikan sebagai individu yang memberikan kepedulian, perlindungan dan arahan sejak bayi hingga tumbuh dewasa. Selama berperan memberi perawatan, arahan dan memenuhi kebutuhan anak, orang tua sangat dipengaruhi oleh budaya dan lokasi geografis. Maka dari itu, peran dan keterlibatan orang tua dalam praktik mengasuh anak bersifat unik di setiap daerah/negara.